2019
DOI: 10.1158/1538-7445.sabcs18-pd2-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD2-01: Personalized serial circulating tumor DNA (ctDNA) analysis in high-risk early stage breast cancer patients to monitor and predict response to neoadjuvant therapy and outcome in the I-SPY 2 TRIAL

Abstract: ctDNA analysis offers a non-invasive approach for monitoring response and resistance to treatment. Serial ctDNA testing during neoadjuvant therapy (NAT) may provide early indicators of emerging resistance and disease progression. In this study, we analyzed ctDNA from high-risk early breast cancer patients who received NAT and definitive surgery in the I-SPY 2 TRIAL (NCT01042379). We hypothesize that (1) assessment of ctDNA levels early in treatment will improve the performance of molecular and imaging-based pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…On the other hand, ctDNA presence was not significantly associated with pCR or EFS neither at 2 weeks after the treatment start, nor before surgery [75]. Consistent results were reported by a translational sub-study of the I-SPY 2 trial, where high ctDNA at the pre-neoadjuvant time point was associated with tumor burden, aggressive biology and subtype, while the presence of ctDNA at post treatment time point was associated with low pCR [76].…”
Section: Neo-/adjuvant Settingsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, ctDNA presence was not significantly associated with pCR or EFS neither at 2 weeks after the treatment start, nor before surgery [75]. Consistent results were reported by a translational sub-study of the I-SPY 2 trial, where high ctDNA at the pre-neoadjuvant time point was associated with tumor burden, aggressive biology and subtype, while the presence of ctDNA at post treatment time point was associated with low pCR [76].…”
Section: Neo-/adjuvant Settingsupporting
confidence: 81%
“…Magbanua et al [76] Retrospective-prospective analysis of the I-SPY 2 trial ctDNA levels and exploratory biomarkers 100% of ctDNA-positive pts. at T3 (n = 5) did not achieve a pCR Sotiriou et al [75] Retrospective analysis of the NeoALTTO trial…”
Section: Neoadjuvantmentioning
confidence: 99%
“…At various stages of development, these approaches generally improve on the current limit of detection for ctDNA analysis (~0.1% mutation allele fraction), but each approach has some limitations. Conventional multiplexed PCR-based approaches have been limited by the high background error rates observed (9,22). An alternative is to incorporate UMIs during the first few cycles of PCR to overcome background errors, but this limits molecular conversion because template DNA molecules not incorporated within the first 2-3 cycles are excluded from further analysis (16,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The translational sub-study of the ongoing I-SPY 2 trial demonstrated the significance of serial monitoring of ctDNA in predicting response to neo-adjuvant treatment (61). ctDNA analysis of the NeoALTTO trial demonstrated that the detection of PIK3CA and/or TP53 mutations, in the baseline (before neo-adjuvant therapy) plasma sample was correlated with lower rates of pathological complete response, whereas persistent ctDNA detection both at baseline and after 14 days of neo-adjuvant therapy was significantly associated with the lowest rate of pathological complete response (71,72).…”
Section: Resultsmentioning
confidence: 99%
“…ctDNA dynamics could serve as a predictive biomarker independent of the histology. Indeed, the I-SPY 2 trial reported that early ctDNA dynamics could predict response to neo-adjuvant treatment (61), whereas in the basket trial SUMMIT a decrease in ctDNA HER2 mutation variant allele frequency during treatment with the pan-HER inhibitor neratinib was followed by an increase upon radiographically proven progression (59).…”
Section: Discussionmentioning
confidence: 99%